Low temperature selective catalytic reduction (SCR) of NOx emissions by Mn-doped Cu/Al2O3 catalysts - Yadav D.; Kavaiya A.R.; Mohan D.; Prasad R. (My University, 2025)
The 15 mol% Cu/Al2O3 catalysts with different Mn doping (0.5, 1.0, 1.5, mol%) were prepared using PEG-300 surfactant following evaporation-induced self-assembly (EISA) method. Calcination of precur-sors were performed in flowing air conditions at 500°C. The catalysts were characterized by X-ray Dif-fraction (XRD), X-ray Photoelectron Spectroscopy (XPS), Scanning Electron Microscope Energy Disper-sive X-Ray (SEM-EDX), Fourier Transform Infra Red (FTIR), and N2 physisorption. The catalysts activities were evaluated for H2 assisted LPG-SCR of NO in a packed bed tubular flow reactor with 200 mg catalyst under the following conditions: 500 ppm NO, 8 % O2, 1000 ppm LPG, 1 % H2 in Ar with total flow rate of 100 mL/min. Characterization of the catalysts revealed that surface area of 45.6-50.3 m2/g, narrow pore size distribution (1-2 nm), nano-size crystallites, Cu2+ and Mn2+ phases were principal active components. Hydrogen enhanced significantly selective reduction of NO to N2 with LPG over 1.0 mol % Mn-Cu/Al2O3 giving 95.56 % NO reduction at 150 °C. It was proposed that the synergistic interaction between H2 and LPG substantially widened the NO reduction temperature window and a considerable increase in both activity and selectivity. Negligible loss of catalyst activity was observed for the 50 h of stream on run experiment at 150 °C. The narrow pore size distribution, thermal stability of the catalyst and optimum Mn doping ensures good dispersion of Cu and Mn over Al2O3 that improved NO reduction in H2-LPG SCR system. Copyright © 2017 BCREC Group. All rights reserved.